SECURITY IN COMPUTING & NETWORKING. - Norafida Ithnin, contributor; Obasan Adebola Olukayode, 1966-, contributor; Shabnam Kasra Kermanshahi, 1986-, contributor; Shukor Abd. Razak, contributor; Hassan Chizari, 1975-, editor; Hazinah Kutty Mammi, editor; Hassan Chizari, 1975-, contributor; Mahnoush Babaeizadeh, 1988-, contributor; Majid Bakhtiari, 1961-, contributor; Mazleena Salleh, contributor; Mohd. Aizaini Maarof, contributor; Mohd. Zalisham Jali, contributor; et al. (Johor Bahru, Johor : PENERBIT UTM PRESS, 2015)
Includes bibliographical references and index